Visual Da’wah in the Documentary Film Senja Geunaseh Sayang: A Rhetorical Analysis of Islamic Messages in the Digital Era - Azhari (Pusaka Cendekia Indonesia Foundation, 2026)
The transformation of digital communication has changed the pattern of receiving religious messages among the younger generation. Conventional da'wah that tends to be formal, verbal, and normative is increasingly experiencing challenges in reaching audiences who are used to visual and emotional experiences. This study aims to analyze the construction of da'wah rhetoric in the documentary film Senja Geunaseh Sayang and evaluate its effectiveness as a visual da'wah medium in the digital era. The research uses a constructivist paradigm with a qualitative-descriptive-analytical approach. The method of analysis integrates Aristotle's rhetorical theory (ethos, pathos, logos), Roland Barthes' semiotics, and modern visual rhetorical concepts. The results of the study show that film builds the dominance of persuasion through pathos (spiritual emotions), strengthened by ethos (the moral authority of the elderly as authentic figures) and logos (implicit normative arguments about birrul walidain). Visual symbols such as twilight, empty space, and silence form an existential metaphor about mortality and family responsibilities. The study concluded that visual da'wah through documentaries is more effective in touching the consciousness of the digital generation because it works through emotional experiences and personal reflection, rather than mere normative instruction. Transformasi komunikasi digital telah mengubah pola penerimaan pesan keagamaan di kalangan generasi muda. Dakwah konvensional yang cenderung formal, verbal, dan normatif semakin mengalami tantangan dalam menjangkau audiens yang terbiasa dengan pengalaman visual dan emosional. Penelitian ini bertujuan menganalisis konstruksi retorika dakwah dalam film dokumenter Senja Geunaseh Sayang serta mengevaluasi efektivitasnya sebagai medium dakwah visual di era digital. Penelitian menggunakan paradigma konstruktivis dengan pendekatan kualitatif deskriptif-analitis. Metode analisis mengintegrasikan teori retorika Aristoteles (ethos, pathos, logos), semiotika Roland Barthes, dan konsep retorika visual modern. Hasil penelitian menunjukkan bahwa film membangun dominasi persuasi melalui pathos (emosi spiritual), diperkuat oleh ethos (otoritas moral lansia sebagai figur autentik) dan logos (argumentasi normatif implisit tentang birrul walidain). Simbol visual seperti senja, ruang kosong, dan kesunyian membentuk metafora eksistensial tentang kefanaan dan tanggung jawab keluarga. Penelitian menyimpulkan bahwa dakwah visual melalui film dokumenter lebih efektif menyentuh kesadaran generasi digital karena bekerja melalui pengalaman emosional dan refleksi personal, bukan instruksi normatif semata.